Optimalization of the Notary Authority in Binding PPJB: Legal Review of the Job Creation Law - Anak Agung Ayu Wina Putri Mayuni; A.A. Ngurah Oka Yudistira Darmadi; Anak Agung Sagung Laksmi Dewi (Fakultas Hukum, Universitas Warmadewa, 2024)
The purpose of this writing is to explain the legal position and role of a Notary in the preparation and approval of land sale and purchase agreements, as required by the legislation. This research focuses on the changes that have occurred in the authority of a Notary, as well as the rights and obligations of the parties involved in making a Sale and Purchase Agreement (PPJB) in accordance with Article 43 paragraph (1) of the Job Creation Law. The research method used is a normative legal approach by analyzing legal regulations and philosophical principles, as well as a prescriptive analysis method. The results of this research confirm that the authority of a Notary in making PPJB is a direct authority granted by the law to a Notary as a public official. This research uses the theory of contract to analyze the legal relationship between the Notary and the parties involved in the contract, while the theory of authority is used to analyze the scope of authority of the Notary in making the contract. The aim of this research is to provide a comprehensive understanding of the dynamics of Notary authority in the context of the Job Creation Law.